MT Escola de Teatro : curso superior em tecnologia em teatro - Ferreira, Flávia Caroline Taques (2024)
MT Escola de Teatro emerged as part of the management goal of Cine Teatro Cuiabá, in the form of a school theater, implemented by the Civil Society Organization named Associação Cultural Cena Onze, selected in the Public Notice of the State Secretariat for Culture, Sports and Leisure n. 01/2016. This research develops a historical and autoethnographic record of this experience of managing public spaces by a Civil Society Organization, by joining efforts with everyone involved, including the State Secretariat for Culture, Sports and Leisure of Mato Grosso (SECEL-MT), the University of the State of Mato Grosso (UNEMAT), the Cena Onze Cultural Association, teachers, students and graduates. The training of students as theater technologists, with an emphasis on acting, directing, dramaturgy, scenery and costumes, lighting, sound design and cultural production, after a 2-year course, has allowed, in addition to the academic qualification of artists, which is precarious in Mato Grosso, continued training and professionalization of the category, with the training and updating of artists.